Implementation Of Baamboozle Game Based Learning To Increase Student Participation In Basic Culinary Learning SMK.N 2 Malang - Citra Diah Permata; Laili Hidayati (Universitas Negeri Padang, 2026)
Conventional one-directional instruction tends to reduce student motivation and engagement, particularly in vocational foundational subjects at the secondary level. This study analyzes the implementation of Baamboozle as a game-based learning medium in Grade X Culinary class at SMKN 2 Malang. The research subjects were 35 class X Culinary students and 1 subject teacher, with a focus on learning the Basics of the Expertise Program subject. Data were collected through participatory observation and in-depth interviews, then analyzed qualitatively descriptively which includes data reduction, data presentation, and drawing conclusions. The findings reveal two key outcomes: first, Baamboozle -based group game activities consistently stimulated active participation and peer collaboration that was absent in conventional instruction; second, students demonstrated measurably improved conceptual understanding, evidenced by faster and more accurate responses during evaluation sessions. Baamboozle is proven effective in creating a learning environment that is engaging, interactive, and responsive to the learning characteristics of Generation Z students. These findings suggest that integrating game-based platforms such as Baamboozle offers a concrete strategy for vocational teachers seeking to foster meaningful, student-centered learning experiences.